(untitled) (REMUNOM, 2025)
Abstract Valuing racial identity in early childhood education is fundamental to combating prejudice and promoting respect for diversity. This article analyzes how children’s literature can be used as a pedagogical tool to strengthen the racial identity of Black children, based on Ana Maria Machado’s book "Menina Bonita do Laço de Fita." The research adopts a qualitative approach, with an interpretive analysis of the work and is supported by theoretical frameworks on anti-racist education, racial identity, and children’s literature, as well as Law No. 10.639/03. The book’s narrative presents a Black character valued for her beauty, promoting self-esteem, representation, and the breaking of stereotypes. The article also shares a personal experience of racism in childhood, highlighting the emotional impact of these experiences and the importance of addressing them early. In addition to the main work, books such as "Sulwe" and "The Little Black Prince" are mentioned, which also contribute to the construction of identity and self-esteem in Black children. The work highlights the importance of educators’ role in mediating these issues and building an anti-racist pedagogy. A project carried out at CEIM Aurora Nunes is also cited as a practical example of promoting ethnic-racial diversity. The conclusion is that children’s literature, combined with pedagogical projects and initiatives, is essential for Black children to positively recognize themselves and for white children to learn to respect differences, contributing to a more inclusive and respectful school environment.